Analisis Sektor Unggulan Di Wilayah Kabupaten Madiun Tahun 2011-2015 - HASTUTI, PUJI; , Drs. Triyono, M.Si (2017)
This study entitled "Analysis of Commodity Sectors in Developing Economy In Madiun Regency Year 2011-2015". This study has the objective to determine the basic sector and non economic base in the district of Madiun, as well as to determine the shift in the economic sector in the district of Madiun. The data used in this research is secondary data obtained from BPS BPS Madiun County and East Java Province. The data in the form of Gross Regional Domestic Product (GRDP) Madiun County and Gross Domestic Product (GDP) of East Java province on the basis of constant prices 2011-2015. The analysis tool used is LQ and Shift Share Esteban Marquillas. LQ analysis research results show that the sector is perfectly located in Madiun County Agricultural sector; sector Water, Waste Management and Recycling; Construction sector; Information and Communications sector; Financial Services and Insurance sectors; Government Administration sector; Educational Services sector; Services sector Health and Social Work; and Other Services sector. The sectors that have competitive advantages and specialized in Madiun County by Esteban Marquillas shift share analysis is the agriculture sector; sector Water, Waste Management and Recycling; Construction sector; Information and Communications sector; Financial Services and Insurance sectors; Real Estate; Government Administration sector; and Other Services.